Global cardiovascular risk and obesity in first level care patients - Agustín Paramio Rodríguez; Ediunys Carrazana Garcés; Myder Hernández Navas; Luis Gustavo Rivero Villalba (Universidad de Ciencias Médicas de La Habana, 2022)
Introduction: Estimating global cardiovascular risk is the best tool for prioritizing the primary prevention of cardiovascular diseases. The risk of cardiovascular disease increases with increasing body weight. Objective: To determine the global cardiovascular risk and to relate it to obesity in first level care patients. Material and Methods: A descriptive cross-sectional study was carried out. The study universe consisted of 803 people; a sample of 585 people was drawn from the three study groups between January 2016 and October 2018. The calculation of global cardiovascular risk was performed according to the criteria specified in the World Health Organization tables. It was related to waist circumference and body mass index. Results: The results show that 51,28 % of the people studied presented a low global cardiovascular risk level; followed by a moderate risk level (29,92 %) and high, very high, and extremely high risk levels (18,80 %). Similarly, 10,94 % are obese people, of whom 42,19 % were distributed between high, very high and extremely high risk levels. Also, 21,20 % of the people studied presented a very high risk according to the waist circumference classification. Conclusions: A low global cardiovascular risk level predominated in the study. As age advances, the global cardiovascular risk increases, with a predominance of males. Obesity was related to global cardiovascular risk.